1997
DOI: 10.1086/304234
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Sapphires: The Properties and Origins of Presolar Al2O3in Meteorites

Abstract: Thirty-seven isotopically highly anomalous presolar grains and one presolar grain Al 2 O 3 MgAl 2 O 4 from a separate of the Tieschitz H3.6 ordinary chondrite were identiÐed out of 17,000 isotopically normal refractory oxide grains by an automatic 16O/18O low mass resolution ion-imaging mapping technique in the ion microprobe. Eight additional presolar grains were found by high mass resolution Al 2 O 3 ion probe measurements of all three stable O isotopes in individual grains, including several that would have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
335
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(353 citation statements)
references
References 93 publications
14
335
1
3
Order By: Relevance
“…The adopted grain size range is motivated by studies on pre-solar grains (e.g. Nittler et al 1997;Daulton et al 2003;Clayton & Nittler 2004) and detailed radiative modeling of evolved stars such as IRAS 17150-3224 and HD 161796 (Meixner et al 2002). The default model corresponds to model 1 in Table 1.…”
Section: Parameter Study: Results and Discussionmentioning
confidence: 99%
“…The adopted grain size range is motivated by studies on pre-solar grains (e.g. Nittler et al 1997;Daulton et al 2003;Clayton & Nittler 2004) and detailed radiative modeling of evolved stars such as IRAS 17150-3224 and HD 161796 (Meixner et al 2002). The default model corresponds to model 1 in Table 1.…”
Section: Parameter Study: Results and Discussionmentioning
confidence: 99%
“…The circumstellar Al 2 O 3 -grains are relatively abundant in meteorites (Nittler et al 1997), albeit perhaps not as abundant as one would expect if all aluminium would condense in these grains (Alexander 1997). This result from meteorite studies now gets some support by our analysis of the ALMA data, confirming that a fraction of the aluminium is still present in its gaseous form after its passage through the dust formation region.…”
Section: Aluminium Depletion Into Grainsmentioning
confidence: 99%
“…Studies of meteorite matrix and IDPs have shown that, at a minimum, the following materials are present at some level in interstellar dust: nanodiamonds (Lewis et al 1989;Bernatowicz et al 1990), poorly graphitized carbon (Amari et al 1990), amorphous carbonaceous materials (Zinner 1988 (Huss et al 1994;Nittler et al 1997;Zinner et al 2003;Stroud et al 2004), and crystalline and amorphous silicates (Bradley 1994;Messenger et al 2003;Nguyen & Zinner 2004). Given that a large fraction of the material in the meteorite matrix is of nebular origin (Boynton 1985;Clayton 1985) it is surprising that any presolar grains survived at all.…”
Section: Pre-solar Grainsmentioning
confidence: 99%